Plyometric Long Jump Training With Progressive Loading Improves Kinetic and Kinematic Swimming Start Parameters. Issue 9 (September 2016) - Rebutini, Vanessa Z.; Pereira, Gleber; Bohrer, Roberta C.D.; Ugrinowitsch, Carlos; Rodacki, André L.F.
Abstract : Abstract: Rebutini, VZ, Pereira, G, Bohrer, RCD, Ugrinowitsch, C, and Rodacki, ALF. Plyometric long jump training with progressive loading improves kinetic and kinematic swimming start parameters. J Strength Cond Res 30(9): 2392–2398, 2016—This study was aimed to determine the effects of a plyometric long jump training program on torque around the lower limb joints and kinetic and kinematics parameters during the swimming jump start. Ten swimmers performed 3 identical assessment sessions, measuring hip and knee muscle extensors during maximal voluntary isometric contraction and kinetic and kinematics parameters during the swimming jump start, at 3 instants: INI (2 weeks before the training program, control period), PRE (2 weeks after INI measurements), and POST (24–48 hours after 9 weeks of training). There were no significant changes from INI to PRE measurements. However, the peak torque and rate of torque development increased significantly from PRE to POST measurements for both hip (47 and 108%) and knee (24 and 41%) joints. There were significant improvements to the horizontal force (7%), impulse (9%), and angle of resultant force (19%). In addition, there were significant improvements to the center of mass displacement (5%), horizontal takeoff velocity (16%), horizontal velocity at water entrance (22%), and peak angle velocity for the knee (15%) and hip joints (16%). Therefore, the plyometric long jump training protocol was effective to enhance torque around the lower limb joints and to control the resultant vector direction, to increase the swimming jump start performance. These findings suggest that coaches should use long jump training instead of vertical jump training to improve swimming start performance.